2002
DOI: 10.1007/bf03218300
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide-co-N-vinylpyrrolidone) as a novel implant materials: Preparation and thermo-gelling behavior

Abstract: Synthesis of polymers with controlled thermosensitive properties was carried out by conventional radical copolymerization of N-isopropylacrylamide (NIPAAm) with N-vinylpyrrolidone (NVP) taken as a hydrophilic comonomer. Lower activity of NVP rather than NIPAAm was revealed by gravimetric and 1 H NMR analysis. Thermosensitive properties of the copolymers were investigated. It was found that aqueous solutions of the copolymers undergo thermo-induced phase transition and become opaque, precipitate or gel with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In common embolic liquids, the entrapment of the radiopaque agent into the polymer network cannot be ensured and its sedimentation during injection or release into the surrounding areas might occur, which would be a major drawback for clinical follow-up and could lead to toxic side effects [15]. So VP was chosen as a third comonomer due to its well-known biocompatibility, non-toxicity, non-immunogeneticity, hydrophilicity and good complexation ability [16]. It was expected that the VP moieties could form complexes with radiopaque agent, Iohexol used in our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In common embolic liquids, the entrapment of the radiopaque agent into the polymer network cannot be ensured and its sedimentation during injection or release into the surrounding areas might occur, which would be a major drawback for clinical follow-up and could lead to toxic side effects [15]. So VP was chosen as a third comonomer due to its well-known biocompatibility, non-toxicity, non-immunogeneticity, hydrophilicity and good complexation ability [16]. It was expected that the VP moieties could form complexes with radiopaque agent, Iohexol used in our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Thermogels are formed during the physical conversion of sol-gel stimulated by changes in temperature [31][32][33]. Polymers that undergo thermogelation are based on natural polymers such as chitosan, hyaluronic acid, gelatin, and amylopectin [29,32], or synthetic ones such as amphiphilic block copolymers of poly(ethylene oxide) (PEG) and poly(propylene oxide) (PPG) [34], PEG-b-polyester copolymers where the polyester can be polylactide (PLA), polyglycolide (PGA), poly(lactide-co--glycolide) (PLGA) or polycaprolactone (PCL) [34][35][36], polymers based on N-isopropylacrylamide (PNIPAM) [37][38][39][40][41], and polymers based on oligo(ethylene glycol) methacrylates [42][43][44][45][46][47][48][49][50].…”
Section: Polymeric Carriers Of Therapeutics: Conjugates Nanoparticlementioning
confidence: 99%
“…A carrier constructed with pure PNIPAAm is difficultly modulated by temperature changes under physiological conditions, and thus, it is essential to tailor the LCST of PNIPAAm-based materials, especially to increase the transition temperature (11), which is helping to expand the potential for future marketable applications. Previous studies have demonstrated that the addition of hydrophilic comonomers leads to the increase of LCST of thermosensitive polymers, while the incorporation of hydrophobic comonomers generally results in the decrease of LCST (6,9,(11)(12)(13). Therefore, the LCST of thermosensitive polymers could be controlled by adjusting their relative hydrophobicity/hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%